Structural surface overlap and derivational complexity in crosslinguistic transfer: Acquisition of English genitive alternation by Egyptian Arabic-speaking learners. (October 2020) - Azaz, Mahmoud
This article adopts the surface overlap and derivational complexity hypotheses to study crosslinguistic transfer in the adult second language (L2) acquisition of English genitive alternation (between the s-genitives and the of genitives) by intermediate and advanced Egyptian Arabic-speaking learners. While the s -genitive (e.g. the boy's shirt ) and the of -genitive (e.g. the shirt of the boy ) are allowed in principle to denote possession, the s -genitive is the native option when the possessor is human and the possessum is nonhuman. In standard syntactic analyses, the s -genitive is held to be more complex than the of -genitive, since it involves raising the possessor in the determiner phrase (DP). Egyptian Arabic is also known for its genitive alternation; it uses the synthetic genitive (the construct state), and the analytic genitive (the free state) that both overlap partially or significantly with the of -genitive. The results of an elicited production task showed that the intermediate group tended to produce the of -genitives in contexts in which the s -genitives were the target construction. The advanced group, on the other hand, produced the more complex s -genitives. These findings suggest that the surface overlap involved between the of -genitives and the corresponding genitive constructions in Egyptian Arabic conspired to trigger this crosslinguistic transfer. Also, resorting to the overlapping of -genitive option can be viewed as a strategy to avoid the more complex s -genitive option. The results of the advanced group imply that the acquisition of English genitive alternation undergoes two developmental stages. In the first, learners favor the less complex and overlapping of -genitives. In the second, they acquire the syntactic derivation in the s -genitives that raises the possessor in the DP.